Evaluation of a candidate breast cancer associated SNP in ERCC4 as a risk modifier in BRCA1 and BRCA2 mutation carriers. Results from the Consortium of Investigators of Modifiers of BRCA1/BRCA2 (CIMBA) - Osorio, A.; Milne, R. L.; Pita, G.; Peterlongo, P.; Heikkinen, T.; Simard, J.; Chenevix-Trench, G.; Spurdle, A. B.; Beesley, J.; Chen, X.; Healey, S.; Neuhausen, S. L.; et al. (British journal of cancer, 2009)
BACKGROUND In this study we aimed to evaluate the role of a SNP in intron 1 of the ERCC4 gene (rs744154), previously reported to be associated with a reduced risk of breast cancer in the general population, as a breast cancer risk modifier in BRCA1 and BRCA2 mutation carriers. METHODS We have genotyped rs744154 in 9408 BRCA1 and 5632 BRCA2 mutation carriers from the Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA) and assessed its association with breast cancer risk using a retrospective weighted cohort approach. RESULTS We found no evidence of association with breast cancer risk for BRCA1 (per-allele HR: 0.98, 95% CI: 0.93-1.04, P = 0.5) or BRCA2 (per-allele HR: 0.97, 95% CI: 0.89-1.06, P = 0.5) mutation carriers. CONCLUSION This SNP is not a significant modifier of breast cancer risk for mutation carriers, though weak associations cannot be ruled out.